Fungal Biofilms: Targets for the Development of Novel Strategies in Plant Disease Management - Villa, Federica; Cappitelli, Francesca; Cortesi, Paolo; Kunova, Andrea (Frontiers in Microbiology, 2017)
The global food supply has been facing increasing challenges during the first decades of the 21st century. Disease in plants is an important constraint to worldwide crop production, accounting for 20–40% of its annual harvest loss. Although the use of resistant varieties, good water management and agronomic practices are valid management tools in counteracting plant diseases, there are still many pathosystems where fungicides are widely used for disease management. However, restrictive regulations and increasing concern regarding the risk to human health and the environment, along with the incidence of fungicide resistance, have discouraged their use and have prompted for a search for new efficient, ecologically friendly and sustainable disease management strategies. The recent evidence of biofilm formation by fungal phytopathogens provides the scientific framework for designing and adapting methods and concepts developed by biofilm research that could be integrated in IPM practices. In this perspective paper, we provide evidence to support the view that the biofilm lifestyle plays a critical role in the pathogenesis of plant diseases. We describe the main factors limiting the durability of single-site fungicides, and we assemble the current knowledge on pesticide resistance in the specific context of the biofilm lifestyle. Finally, we illustrate the potential of antibiofilm compounds at sub-lethal concentrations for the development of an innovative, eco-sustainable strategy to counteract phytopathogenic fungi. Such fungicide-free solutions will be instrumental in reducing disease severity, and will permit more prudent use of fungicides decreasing thus the selection of resistant forms and safeguarding the environment.